Analisis Konsep Pendidikan Anak Dalam Surat Luqman Ayat 12-19 Menurut Tafsir Ibnu Katsir Dan Relevansinya Dengan Pendidikan Remaja Di Era Digital - Adi Yulianto; Wildan Zainun Naim; Roni Langgeng Sutopo; Eko Widiawan; Risca Rahmawati; Syarifah Hanifata Zahro (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
The rapid development of digital technology has created significant challenges for adolescent education, particularly in shaping moral values, spiritual awareness, and responsible social behavior. Adolescents in the digital era are increasingly exposed to unrestricted information, social media influences, and moral degradation, which require educational approaches grounded in strong ethical and religious values. This study aims to analyze the concept of child education in Surah Luqman verses 12–19 according to the interpretation of Ibnu Katsir and to examine its relevance to adolescent education in the digital era. This research employed a qualitative approach using library research methods. The primary data sources consisted of the Qur’an, Tafsir Ibnu Katsir, and various scholarly journals and academic literature related to Islamic education and adolescent development in the digital age. Data were collected through documentation and literature review techniques and analyzed using content analysis. The findings reveal that the educational concepts contained in Surah Luqman verses 12–19 include the values of monotheism education, worship education, moral education, social ethics, patience, humility, and responsibility. These values are highly relevant to adolescent education in the digital era, particularly in developing religious character, self-control, digital ethics, critical thinking, and wise use of technology and social media. The study implies that Qur’anic educational values can serve as an important foundation for building morally responsible and spiritually aware adolescents amid the rapid advancement of digitalization. Furthermore, this research contributes to the development of Islamic education studies and provides practical guidance for parents, educators, and institutions in implementing character education based on Qur’anic teachings in modern society.